Understanding Muslim Social Arrangement: The Pangals of Manipur, India (American Journal of Islam and Society, 2010)
This article analyzes the Muslim Pangal community of Manipurin northeastern India. Although its members have been fairlyintegrated with other groups, their liberal cultural sense, infusedwith a deep religious grounding, has allowed them to borrow variouscultural traits, including language. Apart from Islam, theircultural whole is based on, among other elements, language,dressing patterns, social arrangements, folk songs, and courtshiprituals.